Analysis of strains of Campylobacter fetus by pulsed-field gel electrophoresis. - Fujita, M (1995)
Campylobacter fetus chromosomal DNA from 21 strains was analyzed by pulsed-field gel electrophoresis. The fingerprint patterns generated with SmaI and SalI were distinctive. Using the profiles obtained by pulsed-field gel electrophoresis, we established the phylogenetic dendrogram of C. fetus to identify the genetic relationship of the strains.